2016
DOI: 10.1016/j.jpha.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A novel surface molecularly imprinted polymer as the solid-phase extraction adsorbent for the selective determination of ampicillin sodium in milk and blood samples

Abstract: Surface molecularly imprinted polymers (SMIPs) for selective adsorption of ampicillin sodium were synthesized using surface molecular imprinting technique with silica gel as a support. The physical and morphological characteristics of the polymers were investigated by scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), elemental analysis and nitrogen adsorption–desorption test. The obtained results showed that the SMIPs displayed great adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 29 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…In addition, because of desirable magnetic properties (15 emu/g), it is easier to separate sorbent from sample and realize recycling than nonmagnetic MOF. From the analytical aspect, the linear range and LOD of the proposed method were approximately the same or better than those of some other methods, which represents the promising future of our present MMOF for determination of AMP from complicated cow milk samples [ 3 , [41] , [42] , [43] ] ( Table 3 ). Moreover, the prepared MMOF was compared with some commercial sorbents presented in Table 4 [ [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ].…”
Section: Resultsmentioning
confidence: 72%
“…In addition, because of desirable magnetic properties (15 emu/g), it is easier to separate sorbent from sample and realize recycling than nonmagnetic MOF. From the analytical aspect, the linear range and LOD of the proposed method were approximately the same or better than those of some other methods, which represents the promising future of our present MMOF for determination of AMP from complicated cow milk samples [ 3 , [41] , [42] , [43] ] ( Table 3 ). Moreover, the prepared MMOF was compared with some commercial sorbents presented in Table 4 [ [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ].…”
Section: Resultsmentioning
confidence: 72%
“…In the case of CLO removal by modified silica particles, Du et al () reported that the maximum adsorption capacity of the particles was 6.5 mg/g per gram of adsorbent. In other studies, Li et al () and Wu et al () reported that one gram of MIP particles synthesised for ampicillin can adsorb 13.5 mg of the antibiotic. Compared to these cases, the polymer particles prepared in this study are much more efficient.…”
Section: Resultsmentioning
confidence: 95%
“…However, the Cu‐IIP1 and NIP1 showed the same trend, and the fluctuation bar graphs might be the low concentration of HPMC occurred hydrogen bonding with methacrylic acid and produced the random cavity in the polymer . The adsorption amount of Cu‐IIPs toward Cu 2+ ions immediately increased with the increase of the concentrations of Cu 2+ solution in the initial concentration resulting from the recognition cavities during the imprinting process …”
Section: Resultsmentioning
confidence: 99%